Foot-and-mouth disease virus-like particle vaccine incorporating dominant T and B cell epitopes: enhanced immune response in piglets with CD154 molecules - Li, Yuwan; Zeng, Weijun; Niu, Xinni; Yuan, Zhongmao; Li, Shurou; Lin, Jinru; Xie, Kaiyuan; Zhu, Zixiang; Yi, Lin; Ding, Hongxing; Zhao, Mingqiu; Fan, Shuangqi; et al. (Frontiers in Veterinary Science, 2025)
IntroductionFoot-and-mouth disease (FMD) is a highly contagious disease caused by FMDV, resulting in vesicular lesions in cloven-hoofed animals and posing significant economic threats to the livestock industry. VLP vaccines, which lack viral genetic material and are non-infectious, demonstrate superior safety compared to traditional inactivated vaccines. This study employs ADDomer, a novel adenovirus-based VLP framework, to display FMDV antigenic epitopes on the VLP surface. Additionally, FMDV capsid proteins can assemble into VLPs, offering innovative approaches for developing more efficient and safer FMDV vaccines.MethodsTwo FMDV VLP proteins were constructed using a baculovirus expression system. One VLP was developed by embedding the B-cell epitope of FMDV VP1 into the G-H loop of VP3 and co-expressing it with VP1 and VP0 to form VP1-VP3B-VP0. The other VLP, ADDomer-BBT, fused B-and T-cell epitopes from FMDV O-type VP1 into the ADDomer platform, with porcine CD154 expressed as an immune enhancer. Expression conditions were optimized, and proteins were purified. The VLPs, combined with porcine CD15 molecular adjuvant, were evaluated for immunogenicity in piglets.ResultsAfter purification, both VLPs displayed virus-like structures under electron microscopy. Immunization in piglets induced high levels of FMDV-specific and neutralizing antibodies, enhanced cytokines IL-2, IL-4, and IFN-γ, and increased lymphocyte proliferation. The CD154-added group showed higher immune responses.DiscussionThe VLP vaccines effectively induced strong cellular and humoral immune responses, with CD154 enhancing efficacy. These findings provide insights for developing safer, more effective FMDV vaccines and contribute to advancing livestock health and productivity.